KARAKTERISTIK ROTI TAWAR KAYA SERAT YANG DISUBSTITUSI MENGGUNAKAN TEPUNG AMPAS KELAPA - Deni Antra Pusuma; Yhulia Praptiningsih; Miftahul Choiron (Faculty of Agricultural Technology, University of Jember, 2018)
Indonesia's wheat imports reached 7.49 until 8.10 million tons or ranked second world after Egypt based on data from the Department of Agriculture of the United States (USDA) in the year of 2014/2015/2016. By 2020, projected wheat imports will be increase threefold from the previous year. The consumption of wheat flour in bread production could be decreased by coconut dregs flour as substitute of wheat flour. The research was formulated the fiber-rich white bread using wheat flour and coconut dregs flour with ratio 100%:0%, 95%:5%, 90%:10%, 85%:15%, and 80%:20%. The aim of this research was to know the physical, chemical, sensory properties and crude fiber content of white bread with good quality and high preference. The result showed that the substitution of coconut dregs flour was 10%. The bread had an inner and outer texture of 54.80±0.8 g/10 mm and 195.03±0.86 g/10 ml; lightness of 23.64; loaf volume bread of 147.27±1.4%; uniform slice appearance; moisture content of 39.07±0.12%; ash content of 1.47±0.15%; protein content of 9.59±0.3%; fat content of 6.13±0.49%; carbohydrate content about 44.11±0.72%; crude fiber content about 5.69%; score of preference color, aroma, taste, texture and overall respectively about 5.37; 5.30; 5.27; 5.50; 5.43 (rather like to like). Keywords: coconut dregs flour, crude fiber, white bread